Modifying Thermal and Structural Characteristics of CuAlFeMn Shape Memory Alloy and a Hypothetical Analysis to Optimize Surface-Diffusion Annealing Temperature - Canbay, Canan Aksu; Karaduman, Oktay; Ozkul, Iskender; Unlu, Nihan (Springer, 2020)
In this experimental research study, quaternary Cu-based shape memory alloy with a chemical composition of 73.23Cu-21.93Al-3.36Fe1.48Mn (at.%) and a valence electron concentration (e/a) value of 1.487 was produced by arc melting method. After production, the identical samples of alloy were all subjected to thermal aging at 150 degrees C for 1 h and then cooled in different coolant materials. A varied number of thermal and structural tests and analyses were carried out successfully to study the alterations in the alloy samples and to see the effects of the aging and quenching/cooling media on alloy's characteristic martensitic transformation temperatures, eutectoid points, some other kinetic parameters, and structural features. Among these tests, the DSC analyses showed the variations between the thermodynamical parameters such as the martensitic transformation temperatures of the alloy samples that occurred due to the effects of both aging and various quenching environments. Differential thermal analysis (DTA) measurements showed that some eutectoid point shifts (similar to 20-25 degrees C) occurred on the DTA thermograms of the alloy samples which happened mainly due to the thermal aging. A detailed hypothetical analysis and discussion related to the eutectoid temperature made upon DTA results, since the eutectoid temperature has a key role in some thin-film SMA applications for selecting optimum annealing temperature to make good diffusion of the metal layer on the semiconductor surface without causing a deterioration occurs in SMA properties. The results of structural XRD tests showed that the main martensite peak, the intensities of all peaks, and crystallite size values were changed by the effect of aging. In addition, the intensities of all peaks and crystallite size values were also changed by thermal aging and also by quenching the alloy samples in different environments. All obtained results have reflected that modifying the characteristic parameters of this CuAlFeMn SMA by such ways used here may be helpful in various macroscale SMA-based applications and also in designing miscellaneous micro/nanoscale electromechanical systems (MEMS and NEMS) where different modified SMA properties have been demanding.
Keywords: annealing temperature; CuAlFeMn; eutectoid point; martensite; quenching medium; shape memory alloy; thermal aging